Daniel Defoe : ambition & innovation - Backscheider, Paula R., 1943- (Lexington : The University Press of Kentucky, 1986)
In this book, Paula Backscheider considers Daniel Defoe's entire canon as related, developing, and in close dynamic relationship to the literature of its time. In so doing, she revises our conception of the contexts of Defoe's work and reassesses his achievement and contribution as a writer. By restoring a literary context for modern criticism, Backscheider argues the intensity and integrity of Defoe's artistic ambitions, demonstrating that everything he wrote rests solidly upon extensive reading of books published in England, his understanding of the reading tastes of his contemporaries, and h.
COVER; TITLE; COPYRIGHT; CONTENTS; ACKNOWLEDGMENTS; 1. THE BENT AND GENIUS OF THE AGE; 2. POETRY; 3. PAMPHLETS AND POLITICS; 4. THE HISTORIES; 5. THE HISTORICAL NOVELS; 6. CRIME AND ADVENTURE; 7. ROXANA; 8. MELTED DOWN, FILLED WITH WONDERS; NOTES; BIBLIOGRAPHY; INDEX; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Defoe, Daniel, -- 1661?-1731 -- Criticism and interpretation; Defoe, Daniel, -- 1661?-1731; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Criticism, interpretation, etc